2007
DOI: 10.1017/s1751731107703531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grazing pastures with different botanical composition by lambs on rumen fatty acid metabolism and fatty acid pattern of longissimus muscle and subcutaneous fat

Abstract: In order to study the effect of grazing pastures with a different botanical composition on rumen and intramuscular fatty acid metabolism, 21 male lambs were assigned to three botanically different pastures: botanically diverse (BD) (consisting for 65% of a variety of grass species); Leguminosa rich (L) (consisting for 61% of Leguminosae) and intensive English ryegrass (IR) (with 69% Lolium perenne). Pastures were sampled weekly for 12 weeks for analysis of their fatty acid content and composition and on nine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 23 publications
7
34
1
6
Order By: Relevance
“…This may also be due to a higher proportion of white clover in the diet of O lambs. A recent study found a higher proportion of PUFA and a lower proportion of saturated fatty acid (SFA), and therefore a higher PUFA : SFA ratio in subcutaneous fat from lambs grazing a legume-rich pasture compared with lambs grazing a ryegrass pasture (0.155 v. 0.085; Lourenço et al, 2007). We did not find this difference in the intramuscular fat; however, as pointed out by Lourenço et al (2007) and in line with their results on subcutaneous and intramuscular fat depots, subcutaneous fat is more responsive to changes in dietary FA supply or rumen metabolism than intramuscular fat.…”
Section: Discussionmentioning
confidence: 99%
“…This may also be due to a higher proportion of white clover in the diet of O lambs. A recent study found a higher proportion of PUFA and a lower proportion of saturated fatty acid (SFA), and therefore a higher PUFA : SFA ratio in subcutaneous fat from lambs grazing a legume-rich pasture compared with lambs grazing a ryegrass pasture (0.155 v. 0.085; Lourenço et al, 2007). We did not find this difference in the intramuscular fat; however, as pointed out by Lourenço et al (2007) and in line with their results on subcutaneous and intramuscular fat depots, subcutaneous fat is more responsive to changes in dietary FA supply or rumen metabolism than intramuscular fat.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the transfer efficiency of dietary PUFA to (or their concentration in) ruminant-derived food products has been reported to be positively correlated to the vegetation diversity (Collomb et al, 2002;Lourenço et al, 2007;Willems et al, 2014), the proportion of Fabaceae (Cabiddu et al, 2005;Gorlier et al, 2012), and the proportion of herbs (Petersen et al, 2011;Willems et al, 2014) of the grazed pasture lands. In the current study, the experimental enclosures showed a comparable level of vegetation diversity (H' and J' indexes).…”
Section: Milk Yield Gross Composition and Fatty Acid Profilementioning
confidence: 99%
“…For FA analyses of fresh, wilted and ensiled red clover, samples were extracted on the day of sampling with chloroform/methanol (2/1, vol/vol) according to Lourenço et al (2007), using C19:0 as an internal standard. Incubation fluid was stored at 2188C with chloroform/ Ensiled red clover and in vitro biohydrogenation methanol (2/1; vol/vol) before extraction according to Boeckaert et al (2007), using C13:0 as an internal standard.…”
Section: Silagesmentioning
confidence: 99%